2017
DOI: 10.2132/personality.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Body Weight

Abstract: Models of personality and health have grown in complexity as more is discovered about how traits are related to health-related behaviors, morbidity, and mortality. The present article applies a model of personality and health that incorporates longitudinal relations, behavioral and physiological mechanisms, and context to the relation between Five-Factor Model personality traits and body mass index (BMI) and obesity (BMI≥30). Conscientiousness is associated consistently with lower body weight; the relation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 49 publications
2
17
0
4
Order By: Relevance
“…In case personality trait–BMI associations slightly varied from sample to sample, we found that the variation was partly explained by general sample characteristics, such as percent of participants with obesity and prevalence of females in the sample. Sex differences in Extraversion‐BMI associations have been demonstrated previously and were found again in the current study. As novel findings, we reported obesity status moderating the effects of N5: Impulsiveness, C2: Order, and Extraversion.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In case personality trait–BMI associations slightly varied from sample to sample, we found that the variation was partly explained by general sample characteristics, such as percent of participants with obesity and prevalence of females in the sample. Sex differences in Extraversion‐BMI associations have been demonstrated previously and were found again in the current study. As novel findings, we reported obesity status moderating the effects of N5: Impulsiveness, C2: Order, and Extraversion.…”
Section: Discussionmentioning
confidence: 95%
“…The domain‐level associations of BMI with higher Neuroticism and lower Conscientiousness may suggest a role of increased anxious behaviour and decreased self‐control capabilities . However, many details remain hidden in broad domain‐based findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations